The Effect of Carbon Emissions, Corporate Social Responsibility Disclosure, Return on Equity - Boy Frahansah Berutu; Dias Satria; Indri Supriani (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study analyzes the effect of Carbon Emission (CE), Corporate Social Responsibility (CSR), Return on Equity (ROE), and Leverage on bank lending to manufacturing and mining companies listed on the Indonesia Stock Exchange, using the Panel Data Regression Method. With a sample of 15 companies from 2018 to 2022, the results of the study show that CE and CSR do not have a significant effect on bank lending. On the contrary, ROE and Leverage have a significant effect, where ROE has a negative impact and Leverage has a positive impact on bank loans. These findings conclude that banks in Indonesia are still more focused on financial fundamentals in assessing corporate loan applications, without considering environmental and social risks. This study underlines the importance of innovation in credit structures and loan products to include considerations of environmental and social risks in the future, in order to achieve decarbonization targets and the Paris Agreement.